Cognitive Radio Enabled Multi-Channel Access for Vehicular Communications - Jui-Hung Chu; Kai-Ten Feng; Chen-Nee Chuah; Chin-Fu Liu (2010 IEEE 72nd Vehicular Technology Conference - Fall, 2010)
The IEEE 1609.4 standard has been proposed to provide multi-channel operations in wireless access for vehicular environments (WAVE), where all the channels are periodically synchronized into control and service intervals. The communication device in each vehicle will stay at the control channel for negotiation and contention during the control interval, and thereafter switch to one of the service channels for data transmission in the service interval. The inefficiency of WAVE system comes from the fact that half of the time intervals of the service channels remain idle since all the stations are performing message contention within the control channel. In this paper, the cognitive radio-enabled multi-channel access (CREM) protocol is proposed to increase the channel utilization of IEEE 1609.4 standard. Based on the concept of cognitive radio, the vehicular stations are categorized into primary stations with safety-related messages and secondary stations with non-safety information to be delivered. Prioritized channel access is designed in the proposed CREM scheme in order to increase the transmission opportunity of primary stations. Moreover, extended time intervals are granted for primary stations to ensure reliability for data transmission. The enhanced CREM (CREM-E) protocol is proposed to further opportunistically increase the channel utilization of secondary stations. Simulation results show that the proposed CREM-E scheme outperforms the existing IEEE 1609.4 protocol with enhanced channel utilization and smaller waiting time intervals.